2013
DOI: 10.1098/rspb.2012.1890
|View full text |Cite
|
Sign up to set email alerts
|

How does climate change cause extinction?

Abstract: Anthropogenic climate change is predicted to be a major cause of species extinctions in the next 100 years. But what will actually cause these extinctions? For example, will it be limited physiological tolerance to high temperatures, changing biotic interactions or other factors? Here, we systematically review the proximate causes of climate-change related extinctions and their empirical support. We find 136 case studies of climatic impacts that are potentially relevant to this topic. However, only seven ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
614
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 741 publications
(663 citation statements)
references
References 94 publications
11
614
2
9
Order By: Relevance
“…However, conservation actions focused on biotic interactions may fail unless environmental conditions are suitable; thus, it is important to understand when and where a species range is principally controlled by competition or environmental gradients (Urban, Tewksbury, & Sheldon, 2012). Future extinction risk may result from different climate sensitivities, not from biotic interactions, although these factors are seldom considered simultaneously in a single analysis (Cahill et al., 2013). Using a modeling framework that directly accounts for the presence of the red‐backed salamander and accommodates heterogeneity in detecting either species, we find that climate, not competition, is a chief determinant of the lower elevational range limit of the endemic P. shenandoah salamander.…”
Section: Discussionmentioning
confidence: 99%
“…However, conservation actions focused on biotic interactions may fail unless environmental conditions are suitable; thus, it is important to understand when and where a species range is principally controlled by competition or environmental gradients (Urban, Tewksbury, & Sheldon, 2012). Future extinction risk may result from different climate sensitivities, not from biotic interactions, although these factors are seldom considered simultaneously in a single analysis (Cahill et al., 2013). Using a modeling framework that directly accounts for the presence of the red‐backed salamander and accommodates heterogeneity in detecting either species, we find that climate, not competition, is a chief determinant of the lower elevational range limit of the endemic P. shenandoah salamander.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of the causes of contemporary climate change-related extinctions revealed that changes in species interactions are an important cause of population decline (Cahill et al 2013). Many species of plants rely heavily on other species for a number of essential services, such as pollination, seed dispersal, and nutrient provision.…”
Section: Co-migration Of Dependenciesmentioning
confidence: 99%
“…Recent evidence has highlighted that climate change will directly drive population change and extinction primarily through altered species interactions [12,16]. However, the precise climatic drivers underpinning such relationships remain unclear and may differ between leading and trailing range margins [17].…”
Section: Introductionmentioning
confidence: 99%